Social Dynamics in Counseling Groups: Case Studies of Children with Learning Difficulties - Deliati, Deliati; Firman, Firman; Neviyarni, Neviyarni (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
Learning difficulties are a condition of students where the learning process is characterized by obstacles in achieving learning outcomes, so it is a condition where students cannot learn properly. This research uses a qualitative approach with a literature study method. The main goal is to understand social phenomena and make complete observations, so that researchers can develop a deep and complete understanding. The descriptive analysis method is carried out by describing the facts which are then followed by analysis, not just explaining it, but also providing sufficient understanding and explanation. Group tutoring is an activity in a group setting that utilizes group dynamics. In their activities there is interaction with each other to express opinions, provide suggestions and respond. Group guidance activities provide information related to the topics discussed to help individuals achieve optimal development.